Age-Dependent Heterogeneity in the Efficacy of Prophylaxis With Enoxaparin Against Catheter-Associated Thrombosis in Critically Ill Children: A Post Hoc Analysis of a Bayesian Phase 2b Randomized Clinical Trial. Issue 4 (April 2021) - Faustino, E. Vincent S.; Raffini, Leslie J.; Hanson, Sheila J.; Cholette, Jill M.; Pinto, Matthew G.; Li, Simon; Kandil, Sarah B.; Nellis, Marianne E.; Shabanova, Veronika; Silva, Cicero T.; Tala, Joana A.; McPartland, Tara; et al.
Abstract : OBJECTIVES: We explored the age-dependent heterogeneity in the efficacy of prophylaxis with enoxaparin against central venous catheter-associated deep venous thrombosis in critically ill children. DESIGN: Post hoc analysis of a Bayesian phase 2b randomized clinical trial. SETTING: Seven PICUs. PATIENTS: Children less than 18 years old with newly inserted central venous catheter. INTERVENTIONS: Enoxaparin started less than 24 hours after insertion of central venous catheter and adjusted to anti-Xa level of 0.2–0.5 international units/mL versus usual care. MEASUREMENTS AND MAIN RESULTS: Of 51 children randomized, 24 were infants less than 1 year old. Risk ratios of central venous catheter-associated deep venous thrombosis with prophylaxis with enoxaparin were 0.98 (95% credible interval, 0.37–2.44) in infants and 0.24 (95% credible interval, 0.04–0.82) in older children greater than or equal to 1 year old. Infants and older children achieved anti-Xa level greater than or equal to 0.2 international units/mL at comparable times. While central venous catheter was in situ, endogenous thrombin potential, a measure of thrombin generation, was 223.21 nM.min (95% CI, 8.78–437.64 nM.min) lower in infants. Factor VIII activity, a driver of thrombin generation, was also lower in infants by 45.1% (95% CI, 15.7–74.4%). Median minimum platelet count while central venous catheter was in situ was higher in infants by 39 × 10 3 /mm 3 (interquartile range, 17–61 × 10 3 /mm 3 ). Central venous catheter:vein ratio was not statistically different. Prophylaxis with enoxaparin was less efficacious against central venous catheter-associated deep venous thrombosis at lower factor VIII activity and at higher platelet count. CONCLUSIONS: The relatively lesser contribution of thrombin generation on central venous catheter-associated thrombus formation in critically ill infants potentially explains the age-dependent heterogeneity in the efficacy of prophylaxis with enoxaparin. Abstract : Supplemental Digital Content is available in the text.